Extreme wellness at work: Whose body counts in the rise of exceptionalist organisational fitness cultures. (May 2023) - Butcher, Tim; James, Eric P; Bloom, Peter
Management has long concerned itself with controlling workers' bodies, with organisational wellness discourses being its latest fixation. This article's purpose is to introduce and understand 'whose body counts' – a discourse of bodily exceptionalism in performative organisational cultures. Using ethnographic methods, this article presents an analysis of a CrossFit workplace health promotion at an underperforming US corporation, to identify a complex process of empowerment, self-exploitation and disciplinary regulation to produce performative outcomes. This research illustrates how the workplace health promotion generates a pervasive discourse of exceptionalism underpinned by workers' reflexive exploitation, overarched by peer-surveillance and reflexively embraced through extreme individualised performativities. Critically, it is revealed how individuals competitively engage in communicative labour to demonstrate devotion to self-care that is translated into organisational commitment. Specifically, unquestioned discursive ambiguities are shown to cunningly empower limitlessness meritocratic striving that pits workers against each other, creating constant negotiation of 'whose body counts' by subjugating others.